Perspektif Ekonomi Islam Terhadap Transaksi Shopee Paylater - A Muh Syaifuddin; Ruslang Ruslang; Hasriani Hasriani; Supriadi Muslimin (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2022)
This study discusses an overview of Islamic economics on the use of Shopee Paylater transactions in the city of Makassar. The purpose of this study is to reveal an overview of Islamic economics on the practice of using Shopee Paylater transactions in the city of Makassar. This research is a field research with a qualitative approach method, sourced from primary data and secondary data. The results of the study reveal that Shopee Paylater provided by Shopee aims to benefit from user loans. Electronic loans provided by Shopee to users through the Shopee Paylater feature in terms of the Islamic economy are not justified because this feature draws profits from loan proceeds while Islam forbids taking advantage of loans. Loans provided by Shopee Paylater are usurious and contrary to Islamic economic principles.